Bacterial Quorum-Sensing Systems and Their Role in Intestinal Bacteria-Host Crosstalk - Wu, Liang; Luo, Yubin (Frontiers in Microbiology, 2021)
Quorum-sensing (QS) system is a rapidly developing field in which we are gradually expanding our understanding about how bacteria communicate with each other and regulate their activities in bacterial sociality. In addition to collectively modifying bacterial behavior, QS-related autoinducers may also be embedded in the crosstalk between the host and parasitic microbes. In this review, we summarize the current QS studies in the intestinal microbiome and its potential role in maintaining homeostasis under the physiological conditions. Additionally, we outline the canonical autoinducers and their related QS signal-response systems by which several pathogens interact with the host in the pathological conditions, with the goal of building a broader cognition about intestinal bacterial social activity and facilitating novel antimicrobial therapeutic strategies.